(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Work job orders for 196 seed drills collected by HADCO (Hail Agricultural Development Company), Saudi Arabia, were used in this study. The work job orders were classified in terms of the parts used and the cost of each item. Distribution of repair and maintenance as listed in the work-job orders was classified as repairs by 55% while 45% was found to be maintenance. Moreover, Classification of repair and maintenance for parts of seed drills was 66% for rapair jobs and 34% for manitinance jobs. Cost ratio term was developed, by dividing the repair or maintenance cost by the seed drill purchase price. The results indicate that the average cost ratio was affected by annual working area. Also repair and maintenance cost decreased as increasing the number of seed drills every year, and due to the increasing number of working area, the costs increased after about 430 ha/year.